Multiglandular Parathyroid Disease: the Results of Surgical Treatment - E. A. Ilyicheva; G. A. Bersenev; A. V. Zharkaya; D. A. Bulgatov; V. N. Makhutov (Acta Biomedica Scientifica, 2020)
Background. Sporadic multiple gland disease in primary hyperparathyroidism occurs in 7 to 33 % of cases. The absence of specific risk factors, low sensitivity of imaging methods, and low efficiency of bilateral neck exploration and intraoperative monitoring of parathyroid hormone indicate the complexity of the diagnosis and treatment of this disease’s form. Aim of the research. To analyze the results of surgical treatment of multiple lesions of the parathyroid gland in primary and secondary hyperparathyroidism. Methods. There was retrospective study, which included 100 observations of surgical treatment for primary and secondary hyperparathyroidism in the thoracic department of Irkutsk Regional Clinical Hospital from May 2018 to September 2019. The main point was to identify the frequency of surgical treatment outcomes in patients with multiple parathyroid lesions. As part of the study, potential predictors of multiple gland disease in primary hyperparathyroidism were analyzed. Results. Multiple gland disease in primary hyperparathyroidism occurs in 29 % of cases and causes persistence of the disease (p ≤ 0.01). Signs of multiple gland disease in primary hyperparathyroidism include the level of ionized calcium, parathyroid hormone (p ≤ 0.05), creatinine level and glomerular filtration rate (p ≤ 0.01). A negative result of intraoperative monitoring correlates with persistence of primary hyperparathyroidism in multiple lesions (χ2, p ≤ 0.05). Selective parathyroidectomy is associated with persistence of hyperparathyroidism in multiple lesions (χ2, p ≤ 0.05), while total parathyroidectomy is associated with remission of the disease (χ2, p ≤ 0.05). We did not find a statistically significant relationship between the results of surgical treatment for morphology of the parathyroid glands (χ2, p > 0.1). Conclusion. Multiple gland disease is the main cause of persistence of primary hyperparathyroidism. This form of the disease corresponds to lower levels of calcium, parathyroid hormone, and kidney function. Persistence factors have been established: removal of less than four parathyroid glands and a negative result of intraoperative monitoring of parathyroid hormone. Bilateral neck exploration does not reduce the incidence of disease persistence.